Patient's Satisfaction on Surgical Services in Some Selected Private Hospitals in Dhaka - Begum, M; Mehedi, MT; Mahmud, A; Sarwar, AFM; Nasreen, A (Bangladesh Medical Journal, 2014)
This was a descriptive type of cross-sectional study conducted in four selected private hospitals in Dhaka city with a view to assessing patient's satisfaction on surgical services. The study period was from March 2004 to June, 2004. The sample size was 110 and selected by purposive sampling technique. Surgical patients were interviewed with a structured questionnaire on the day of discharge or about to be discharged and also hospital record reviewed .for finding the selective patients. The result of study revealed that 87.3% patients were satisfied with surgeon's behavior, 85.5% were satisfied with pre-operative counseling by the surgeons. Regarding doctors services, maximum patients satisfied (91 8%) with doctors behavior. About 54.50% patients were satisfied with their physical examination and 67.30% were satisfied about pre-operative counseling by doctor. Satisfaction on post-operative care by doctors was 70.9%. Regarding nurses services, 71.8% patients were satisfied with their behavior 66.4% were satisfied with their dutifulness. In regard to general cleanliness of hospital 91.8% patients were satisfied while 62.8% were satisfied with cleanliness of toilet. According to this study 73.6% patients were satisfied with post-operative services and 78.2% were satisfied with water supply of hospital. Mean hospital stay of surgical patient as found in this study was 6.26 days with a standard deviation of ±3.58 days. Despite there were certain aspects of dissatisfaction namely inadequate waiting room facility and unclean toilets. Improvements of these areas were recommended. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18952 Bangladesh Medical Journal 2012 Vol.41(3): 15-18